Influenza virion-derived viral ribonucleoproteins synthesize both mRNA and cRNA in vitro. - Vreede, F; Brownlee, G (2007)
The mechanisms regulating the synthesis of mRNA, cRNA, and viral genomic RNA (vRNA) by the influenza A virus RNA-dependent RNA polymerase are not fully understood. Early results suggested that the RNA polymerase "switched" from a transcriptase to a replicase during the viral life cycle in response to the expression of viral proteins. However, recently an alternative model suggesting that replication of influenza virus is regulated by stabilization of the replicative intermediates was proposed. According to this model, the virion-associated polymerase is capable of synthesizing both mRNA and cRNA. We now demonstrate that virion-derived viral ribonucleoproteins (vvRNPs) synthesize both mRNA and cRNA in vitro in the absence of non-virion-associated RNA polymerase or nucleoproteins. The authenticity of the in vitro-transcribed mRNA and cRNA was confirmed by terminal sequence analysis. The addition of non-virion-associated polymerase or NP had no effect on vvRNP activity. De novo synthesis of cRNA was found to be more sensitive than the capped primer-dependent synthesis of mRNA to the concentration of ATP, CTP, and GTP. We conclude that vvRNPs intrinsically possess both transcriptase and replicase activities and that there is no switch in the synthesis of mRNA to cRNA during the influenza virus life cycle.